Effect of temperature on development and survival of the legume pod borer, Maruca vitrata (Fabricius) (Lepidoptera: Pyralidae) reared on a semisynthetic diet - Adati, T.; Nakamura, S.; Tamò, Manuele; Kawazu, K. (Japanese Society of Applied Entomology & Zoology, 2004)
The effect of temperature on the development and survival of the legume pod borer, Maruca vitrata (Fabricius) (Lepidoptera: Pyralidae) was examined by rearing cohorts on a semi-synthetic diet containing cowpea grain and leaf at different constant temperatures in the laboratory. The developmental periods for eggs, larvae and pupae shortened with increasing temperatures from 14.4°C to 29.3°C. The thermal constants and lower thermal thresholds for the development in the egg, larval and pupal stages were 51.1, 234.7 and 116.5 degree-days and 10.5, 10.0 and 10.9°C, respectively. Development was delayed at higher temperatures for all the stages, and the upper thermal threshold was estimated to be in the range of 29.3–31.9°C depending on the developmental stage. At 34.3°C, the survival rates for eggs, larvae and pupae were below 10%, which were lower than those at other temperatures. The development of the larval population in the cowpea field of northern Nigeria was simulated based on daily temperature and the developmental data obtained from the laboratory experiments. The simulated dates of the midpoints in the 4th and 5th instars were concordant with the dates of 50% cumulative field collection for the respective instars. These results would be useful for forecasting pest incidence in the crop fields of the West African savanna.